The Assessment of the Investment Potential of the Insurance Sector of the Region in the Conditions of Risk and Uncertainty - Alekseevna Okorokova, Olga; Konstantinovna Ulibina, Lubov; Alekseevna Maksimenko, Polina; Gennadevich Rusetskiy, Mikhail; Ivanovna Lazareva, Galina (International Journal of Engineering and Technology, 2018)
Krai; the problems of its development are revealed as well. It is proved that in the conditions of risk and uncertainty it is especially important to distinctively define the role of the insurance sector of the financial market, to determine its interaction with the real sector branches of the regional economy by means of using the industrial, social and investment potential. Modern insurance relations are formed under the influence of the transformation processes in the development of the financial system, institutions and instruments of the insurance sector; they are determined by the methods of state regulation as well. Underestimating the problems of the insurance market in the reproduction process of the regional economy negatively affects its development. In this regard it is essential to develop and implement a qualitatively new strategy of the development of the insurance market and its infrastructure that could be oriented towards modern achievements. At the same time the reproductive, investment approach to the insurance strategy should be implemented. The authors have developed a factorial model of the assessment of the investment potential of the regional insurance market in the context of socio-economic transformation of the development institutions. The main vectors of the development of the regional insurance market on the basis of the economic potential of the region are suggested.Â Â